2013
DOI: 10.1021/ma302503w
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and Kinetic Aspects of Coassembly of PEO–PMAA Block Copolymer and DPCl Surfactants into Ordered Nanoparticles in Aqueous Solutions Studied by ITC, NMR, and Time-Resolved SAXS Techniques

Abstract: The electrostatic coassembly of a block copolymer polyelectrolyte poly(ethylene oxide-block-poly-(methacrylic acid), PEO 705 −PMAA 476 , and oppositely charged surfactant, N-dodecylpyridinium chloride (DPCl), has been investigated by a combination of isothermal titration calorimetry (ITC), spin-echo NMR spectroscopy, and timeresolved SAXS measurements. The study (i) confirms the conclusions drawn from our earlier study [Macromolecules 2012, 45, 6474] by scattering and microscopy techniques (i.e., the ITC cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 58 publications
4
37
0
Order By: Relevance
“…With this in mind, isothermal temperature calorimetry (ITC) experiments were run at various temperatures,w here ac oncentrated Na[CoD] solution was slowly titrated into pure water. [32,33] Thea ggregates were decomposed into [CoD] À unimers and the measured process corresponded to deaggregation. Ther aw data is shown in Figure 5.…”
Section: Plots Of Both the Cacvalues For Na[cod] And The Cmc Values Fmentioning
confidence: 99%
“…With this in mind, isothermal temperature calorimetry (ITC) experiments were run at various temperatures,w here ac oncentrated Na[CoD] solution was slowly titrated into pure water. [32,33] Thea ggregates were decomposed into [CoD] À unimers and the measured process corresponded to deaggregation. Ther aw data is shown in Figure 5.…”
Section: Plots Of Both the Cacvalues For Na[cod] And The Cmc Values Fmentioning
confidence: 99%
“…Examples include the cubosomes, 14 which are dispersions of bicontinuous cubic phases studied for their potential for drug delivery. Other more recent examples are from studies reported by Lindman and co-workers, 15 and in the last few years, reports by Uchman 16 have described internally structured particles using the complexation between surfactants and polyions. During the past years, a series of studies have reported the formation of colloidal complexes made from oppositely charged surfactants and charged–neutral block copolymers.…”
Section: Introductionmentioning
confidence: 97%
“…Accordingly, such suprastructures are found in other long chain polysaccharide/surfactant complexes [131][132][133]. In a similar fashion, microphase separation in double hydrophilic blockcopolymer/surfactant mixtures leads to comparable coassembled structures [134][135][136].…”
Section: Chitosan-alkyl Oligooxyethylene Carboxylic Acidsmentioning
confidence: 68%